Evidence for interleukin 17 involvement in severe immune-related neuroendocrine toxicity. (December 2020) - Mazzarella, Luca; Giugliano, Silvia; D'Amico, Paolo; Belli, Carmen; Duso, Bruno Achutti; Rescigno, Maria; Curigliano, Giuseppe
Abstract: Aim: Severe neurological and endocrine toxicities are well recognised adverse events of immune checkpoint inhibitors. However, the underlying pathophysiology is poorly understood, and classical circulating markers are often non-informative, making it difficult to obtain a precise diagnosis and to initiate timely and effective treatment. Here we investigated immune-modulating activity in the plasma of a mesothelioma patient who developed fatal neuroendocrine toxicity characterised by insulin-dependent diabetes, hypophisitis and a myasthenia-like syndrome while on treatment with the dual PD1 and TIM3 blockade. Methods: We used an in vitro functional assay for unbiased detection of plasma dendritic cell–modulating activity, followed by cytokine quantification by the Cytokine Bead Array. Results: Immunosuppressive treatment as per established guidelines could not prevent the fatal outcome. Patient's plasma contained a dendritic cell–stimulating activity that induced specific markers (CD25+) compatible with T-helper 17 stimulation. Consistently, elevated levels of interleukin 17 (IL17A), but no other cytokines, were identified in the patient's plasma but not in controls (healthy volunteers and patients treated with immunotherapy without neuroendocrine toxicities). Conclusion: If confirmed in larger series, these data suggest IL17 as a candidate diagnostic and therapeutic target in the management of high-grade neuroendocrine immune-related adverse events. Highlights: A case of a patient with rare combination of immune-related myasthenia, diabetes mellitus and hypophysitis is presented. Standard management of neuroendocrine immune-related adverse events (IrAEs) was ineffective. The patient's plasma contained a dendritic cell–modulating activity. Levels of IL17 were selectively elevated in the patient compared with those of negative controls. Interleukin 17 may be useful to diagnose and potentially treat neuroendocrine IrAEs.